FROM INTERNATIONAL TO GLOBAL COMMUNICATION AND BACK - Vranješ, Aleksandar (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2018)
The transformation of the international to global communication is over, and its effects are still in the focus of the experts in this field. Modern information and communication technologies, as the primary agent of these transformation, have enabled the expansion of the number of subjects of this form of communication practice. For the first time in the history of mankind, citizens have become actors of both international and global communication, under the condition that they have a right gadget for Internet access, digital literacy, and need and motive to communicate across the borders of national states. Hence, a public debate was opened among the experts in this field as to whether this transformation would lead to a new global order based on the cosmopolitan ideas or to the increase of hegemony, exploitation, subordination from center to periphery. The discovers from the global whistleblowers have given strong arguments to the advocates of this second, "pessimistic" perspective of the development of global communication, opening up a completely new question – whether in the future the states will strive to achieve the so-called cyber or internet sovereignty. In the case that the state's position would be strengthened in the domain of the digital communication regulations, and also in the domain of the restriction and protection of its own communication sovereignty in the online sphere, it is possible that in the near future we will witness the reversible process of the return of international communication.  In that case, the states will again play a primary role as subjects of the global communications and the position of citizens could be either reduced, limited or fully negated, which is the main topic of this paper.
Keywords: citizens; Internet; information-communication technology; transformation; global communication; international communication